Flexi Radio Base Station (RBS) Performance Analysis of Voice and Trafic on Kota 2 Jakarta Barat Base Station Control (BSC) - Ferdian, Mushfar; Zulkifli, Fitri Yuli (UI Scholars Hub, 2005)
Flexi Radio Base Station (RBS) Performance Analysis of Voice and Trafic on Kota 2 Jakarta Barat Base Station Control (BSC). The CDMA 2000 technology uses circuit switch method to handle voice traffic and packet switch method to handle data traffic between the user and RBS (Radio Base Station). These two parameters can be used to measure performance of the network generally, so it is necessary to optimize them. This paper analyze the performance of RBS by measuring its parameters such as set up failure ratio, drop ratio, and occupancy. Furthermore, the traffic increment is calculated too in order to provide information for improvement in the future. Through the analysis, it is realized that a way to improve configuring it uniquely based on its area of scope. Some RBS need soon, but some others don’t. Beside of that, it is also known that the voice communication effectively while data communication roughly.